EDUKASI PRANIKAH DENGAN METODE AUDIO VISUAL TERHADAP PENGETAHUAN DAN PERSEPSI MENIKAH PADA REMAJA - Ahmad, Deni; Ansori, Ansori (P2M STKIP Siliwangi, 2023)
Abstract Indonesia is in seventh place with 1,408,000 cases of early marriage. The West Bandung Child Protection and Family Planning Women's Empowerment Agency (BP3AKB) noted that the rate of early marriage in West Bandung Regency (KBB) is still high, on average in all districts in KBB the rate of early marriage is still in the high category, including Lembang and Padalarang sub-districts. Early marriage is marriage to adolescents under 20 years old who should not be ready to marry. A marriage that is done when a person is not ready physically and mentally has a negative impact. The most experienced impacts were psychological, health, and socio-economic impacts. This early marriage needs to be prevented to reduce the negative impact it produces in society later. One of the efforts to reduce and prevent these negative impacts is by providing targeted education. This research aimed to know the application of premarital education with the audio-visual method, describing the knowledge and perceptions of adolescents before and after education is given and the relationship between changes in knowledge and perceptions of adolescents in Kec. Padalarang Regency. West Bandung after being given premarital education. This research was conducted using the Pre experiment one group pretest-posttest design method with a purposive sampling technique. The sample in this study was 25 adolescents aged 18-25 years. Based on the results of statistical testing, it is known that there is a change in knowledge (p=0.000) and adolescent perceptions (p=0.000) in Kec. Padalarang Regency. West Bandung, which is significant after being given education about premarital with the audio-visual method. Changes in the average value of adolescent knowledge from 10.16 ± 3.21 to 12.16 ± 1.97. At the same time, the average value of adolescent perceptions was from 53.04 ± 5.09 to 56.48 ± 4.61. Premarital education with audio-visual methods is applied to adolescents in Kec. Padalarang Regency. West Bandung is given in the form of a briefing before teenagers continue to the marriage stage in the form of a YouTube video. This premarital educational material contains six aspects. The aspects conveyed in the video are the foundation of marriage, planning for partner selection, the dynamics of married life, the needs of family life, the continuation of quality generations, and family resilience. The aspects presented are packaged in a familiar language and easily understood by teenagers. Keywords:        premarital education, youth, audio-visual media